The Effects of Low-Dose Non-ionizing and Ionizing Radiation on Wound Healing and Cancer - Raahilah, Z. E.; Chew, Ming Tsuey *; Bradley, D.A. *; Peh, Suat-Cheng *; Teow, Sin-Yeang (Springer, Cham, 2022)
Radiation therapy is a vital integrated part of modern comprehensive cancer management. Aside from the typical use of radiotherapy in treatment of cancer, low-dose radiation (LDR), typically <100 mGy, shows the capacity to improve wound healing by promoting fibroblast-to-myofibroblast differentiation, matrix deposition, keratinocyte proliferation and angiogenesis. Moreover, animal studies have shown LDR attenuates systemic acute inflammatory response by regulating inflammatory cytokines, thus alleviating damage associating with chronic diabetic and burn wounds. Wounds can be classified as open or closed. Open wounds, such as cuts, burns or ulcers, can arise from external factors such as accidents, surgery and trauma or internal factors, such as diabetes mellitus, whereas closed wounds may occur due to blunt force trauma. Additionally, wounds can be either acute or chronic, depending on their healing capacity. These disruptions of the skin’s structural and functional integrity go through four distinct phases to achieve complete wound healing, namely, haemostasis, inflammation, cellular migration and proliferation and remodelling. Photobiomodulation and low-dose ionizing radiation have been studied for their effects on the cellular and molecular processes involved in wound healing. Similarly, both methods of low-dose radiation treatment have also been examined for their cancer therapy-associated adverse effects. In this paper, the molecular and cellular effects of low-dose radiation on wound healing and cancer cells are discussed. Additionally, the protective effects of low-dose radiation against conventional cancer treatments such as high-dose radiation and chemotherapy are also discussed.